The epigenetics of epithelial-mesenchymal plasticity in cancer - Tam, Wai Leong; Weinberg, Robert A (Nature medicine, 2013)
Epithelial-mesenchymal transitions (EMTs) are a key requirement for cancer cells to metastasize and colonize in a new environment. Epithelial-mesenchymal plasticity is mediated by master transcription factors and is also subject to complex epigenetic regulation. This Review outlines our current understanding of the interactions between EMT-inducing transcription factors and epigenetic modulators during cancer progression and the therapeutic implications of exploiting this intricate regulatory process. During the course of malignant cancer progression, neoplastic cells undergo dynamic and reversible transitions between multiple phenotypic states, the extremes of which are defined by the expression of epithelial and mesenchymal phenotypes. This plasticity is enabled by underlying shifts in epigenetic regulation. A small cohort of pleiotropically acting transcription factors is widely recognized to effect these shifts by controlling the expression of a constituency of key target genes. These master regulators depend on complex epigenetic regulatory mechanisms, notably the induction of changes in the modifications of chromatin-associated histones, in order to achieve the widespread changes in gene expression observed during epithelial-mesenchymal transitions (EMTs). These associations indicate that an understanding of the functional interactions between such EMT-inducing transcription factors and the modulators of chromatin configuration will provide crucial insights into the fundamental mechanisms underlying cancer progression and may, in the longer term, generate new diagnostic and therapeutic modalities for treating high-grade malignancies.